1996
DOI: 10.1016/0735-1097(96)00129-5
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic and diastolic function assessed with two-dimensional and Doppler echocardiography in “white coat” hypertension

Abstract: The arterial pressure response in subjects with white coat hypertension is associated with increased left ventricular external work, increased end-systolic wall stress and alterations of left ventricular filling but normal ejection fraction and velocity of circumferential fiber shortening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
2
11
2
1
Order By: Relevance
“…It should not, however, be assumed that white coat hypertension is similar to normotension and therefore harmless to the heart 6. In fact more recent studies including larger numbers of normotensive individuals have raised doubts about white coat hypertension as a benign condition 710. This is supported by an epidemiological study that showed an unfavourable risk profile in young adults with white coat hypertension including a high prevalence of familial, haemodynamic, and metabolic risk factors 11…”
Section: Introductionmentioning
confidence: 99%
“…It should not, however, be assumed that white coat hypertension is similar to normotension and therefore harmless to the heart 6. In fact more recent studies including larger numbers of normotensive individuals have raised doubts about white coat hypertension as a benign condition 710. This is supported by an epidemiological study that showed an unfavourable risk profile in young adults with white coat hypertension including a high prevalence of familial, haemodynamic, and metabolic risk factors 11…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] On the other hand, different results have been obtained in other reports. [18][19][20][21][22][23][24][25][26] Various studies have suggested that only about one-half to two-thirds of the variation in the anatomic extent of atherosclerosis and risk for atherosclerotic vascular disease can be explained by classic risk factors. 27,28 Therefore, new risk factors have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Most data indicate that this condition (which occurs in about 10% of the population [18]) represents a lesser cardiovascular risk than the condition characterized by both an office and an ambulatory BP elevation. Conflicting data about prevalence of organ damage, cardiovascular risk and proneness to future hypertension make it uncertain whether or not this represents a truly innocent phenomenon [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. This suggests that caution should be used when deciding whether or not such patients should be treated.…”
Section: Isolated Office (White-coat) Hypertensionmentioning
confidence: 98%